2018
DOI: 10.1093/mnras/sty3462
|View full text |Cite
|
Sign up to set email alerts
|

QUIJOTE scientific results – III. Microwave spectrum of intensity and polarization in the Taurus Molecular Cloud complex and L1527

Abstract: We present new intensity and polarization observations of the Taurus molecular cloud (TMC) region in the frequency range 10-20 GHz with the Multi-Frequency Instrument (MFI) mounted on the first telescope of the QUIJOTE experiment. From the combination of the QUIJOTE data with the WMAP 9-yr data release, the Planck second data release, the DIRBE maps and ancillary data, we detect an anomalous microwave emission (AME) component with flux density S AME,peak = 43.0 ± 7.9 Jy in the Taurus Molecular Cloud (TMC) and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 73 publications
2
17
0
Order By: Relevance
“…Individual examples point to clear leakages of AME into free-free emission and vice versa, which can be seen by eye. However, leakages primarily occur from AME into free-free in this region, which is consistent with QUIJOTE studies of the Taurus region by Poidevin et al (2019) and observations of W43, W44, and W47 by Génova-Santos et al (2017). These leakages originate from degeneracies between components due to the limited multifrequency data available to the Planck Collaboration X (2016a) COMMANDER separation, and they were observed and discussed in Planck Collaboration XXV (2016c) and Planck Collaboration IV (2020b).…”
Section: Commander Comparisonsupporting
confidence: 79%
See 2 more Smart Citations
“…Individual examples point to clear leakages of AME into free-free emission and vice versa, which can be seen by eye. However, leakages primarily occur from AME into free-free in this region, which is consistent with QUIJOTE studies of the Taurus region by Poidevin et al (2019) and observations of W43, W44, and W47 by Génova-Santos et al (2017). These leakages originate from degeneracies between components due to the limited multifrequency data available to the Planck Collaboration X (2016a) COMMANDER separation, and they were observed and discussed in Planck Collaboration XXV (2016c) and Planck Collaboration IV (2020b).…”
Section: Commander Comparisonsupporting
confidence: 79%
“…Finally, by using QUIJOTE and C-BASS, we have shown that the Planck Collaboration X (2016a) COMMANDER separation maps in the region suffer from degeneracies between free-free emission and AME due to the limited frequency coverage of the data used, highlighting the need for data below ≈ 20 GHz as discussed in Génova-Santos et al (2017) and Poidevin et al (2019). The addition of low frequencies emphasizes the importance of cross-collaborations at low frequencies such as QUIJOTE and C-BASS, where the overall outcome far exceeds the sum of their individual contributions.…”
Section: Instrumentmentioning
confidence: 96%
See 1 more Smart Citation
“…The fidelity of our study is likely most limited by the reliability of the AME maps, which result from an extensive and challenging component separation analysis (Planck Collaboration X 2016). While additional multifrequency data have in general validated the Planck Collaboration X (2016) AME maps, systematic discrepancies have been noted at the ∼10-20% level (Dickinson et al 2019;Poidevin et al 2019;Cepeda-Arroita et al 2021). In particular, the AME is often underestimated and free-free emission overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The Thirty and Forty GHz polarimeters for the Q-U-I JOint TEnerife (QUIJOTE) CMB radio astronomy experiment, 1,2 are broadband very sensitive receivers to perform scientific sky observations of the Cosmic Microwave Background (CMB). The aim of the QUIJOTE experiment is the measurement of the linear polarization percentage of the received waves from the sky.…”
Section: Introductionmentioning
confidence: 99%